Analisis Penilaian dan Evaluasi Risiko Keselamatan dan Kesehatan Kerja dengan Metode FMEA pada Pemeliharaan Jaringan Transmisi Listrik di ULTG Lombok Barat - Kusmiati, Sri; Ayu Sri Adnyani, Ida; Perdana Putra, I Ketut (Jurnal Tekno, 2025)
The West Lombok Transmission and Substation Services Unit (ULTG) has an important role in maintaining the electricity transmission network. However, this work has high risks, such as falling from heights, exposure to electromagnetic fields, and extreme environmental conditions. Therefore, this study aims to analyze risks and evaluate work safety control efforts using the Failure Mode and Effect Analysis (FMEA) method. This research uses a qualitative approach through interviews and questionnaires and quantitative with the calculation of Risk Priority Number (RPN). The results of the analysis show that the level of risk at ULTG West Lombok varies from very low (RPN 6.4) to low (RPN 25). The risks include work tool failure and potential worker accidents. To reduce the risks, measures such as the use of Personal Protective Equipment (PPE), implementation of safe work procedures, and regular inspection of tools and tower structures are carried out. Using the FMEA method, this research helps improve work safety and build a culture of Occupational Safety and Health (K3) at ULTG West Lombok.